Fundamental ASSIGNMENT Debora

Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

1(a).

Given
o A and B are finite sets.
o n(A) = M
n(B) = N
To state and prove a formula for n(A x B), where A x B represent the
cartesian product of A and B.
solution1(a)
from,
cartesian product A x B consists of ordered pairs (m, n) where m ∈ A
and n ∈ B. Each element in A pairs with each element in B.
from;
A x B = { (m, n); m ∈ A and n ∈ B }
n(A x B) = { n(A) and n(B) }
n(A x B) = n(A) x n(B)
where by: n(A) = M and
n(B) = N
n(A x B) = M x N
n(A x B) = M ˑ N

The number of element in A x B is the product of the number of
element in A and B
n(A x B) = n(A) x n( B) = n(A) ˑ n(B) = M ˑ N
Qn. 1(b)
Given
A = { x : |x| > 1 }
B = { x2 : 10 ≤ x < 6 }
C={:0<|x|<4}
To find;
(i) (A ∪ B) ∩ C
(ii) (A ∩ B) ∪ C
(iii) (A ∪ C) ∩ B

solution1(b)
from,
o A = { x : |x| > 1 }
since there are no any value that could satisfy the above equation
thus A = ∅
also from,
o B = { x2 : 10 ≤ x < 6 }
again since there are no any value that could satisfy the above
equation
hence B = ∅
again from,
1
o C={ :0<|x|<4}
𝑥
−1 −1 1 1
C={ , , −1, 1, , } these are the values that satisfy the
3 2 2 3
equation
Hence
i) from,
(A ∪ B) ∩ C but A = ∅ and B = ∅
(∅ ∪ ∅) ∩ C definition
∅∩C idempotent law
∅ identity law

(A ∪ B) ∩ C = ∅

ii) also from,


(A ∩ B) ∪ C but A = ∅ and B = ∅
( ∅ ∩ ∅) ∪ C definition
∅∪C idempotent law
C identity law

−1 −1 1 1
(A ∩ B) ∪ C = { , , −1, 1, , }
3 2 2 3

iii) again from,


(A ∪ C) ∩ B but A = ∅ and B = ∅
( ∅ ∪ C) ∩ ∅ definition
C∩∅ identity law
∅ identity law

(A ∩ B) ∪ C = ∅
Qn 2.
Given
{(p ⟶ q) ˄ ( r ⟶ ~s)} ⟶ {(p ⟶ ~q)}
To check using special truth table to test if its valid or not
solution#2
from,
{(p ⟶ q) ˄ ( r ⟶ ~s)} ⟶ {(p ⟶ ~q)}
hypothesis (p ⟶ q) and ( r ⟶ ~s)
conclusion (p ⟶ ~q).
To check the value of the hypothesis (p ⟶ q) and ( r ⟶ ~s) thus
(p ⟶ ~q) is FALSE if p is True and q is True
A special Truth Table
p q r s ~q ~s P ⟶ q R ⟶ ~s P ⟶ ~q

T T T F F T T T F

Therefore, the proposition {(p ⟶ q) ˄ ( r ⟶ ~s)} ⟶ {(p ⟶ ~q)} is


invalid since it is possible to set all the hypothesis TRUE with
conclusion FALSE

You might also like